Didactic strategy based on the use of investigative skills to promote interest in the study - Pérez García, Patricia Marlene (2017)
The present research denominated: Didactic strategy based on the use of investigative abilities to promote the interest for the study in the students of the fifth grade of the educational institution "José Leonardo Ortiz" of Chiclayo, 2016, is an investigation of experimental type that Makes use of the application of diverse strategies in classroom applied directly to students of the fifth grade of secondary to evaluate the effectiveness of the application of didactic strategies based on the use of investigative abilities with the intention to promote the interest by the study and significantly improve the Learning in mathematics through reading and research. The results obtained were positive, in this sense, the statistical treatment of the results obtained in the pretest and posttest was performed by calculating the measures of central tendency and performing the testing of the hypotheses using comparative data between the pre (9, 08) and post test (15,48), resulting in that the students of the experimental group emigrated to have a good qualifier, whose difference is 6.4 points. It is concluded that the application of didactic strategies based on the use of investigative skills promotes the interest in the study of fifth grade students of the José Leonardo Ortiz Educational Institution of the José Leonardo Ortiz district, 2016, accepting the hypothesis of Investigation, which shows that the investigation is valid.